CHARACTERIZATION OF CRUDE EXTRACT POLYPHENOLOXIDASE ENZYME FROM BLACK TIGER SHRIMP (Penaeus monodon) - Made Suhandana; Tati Nurhayati; Laksmi Ambarsari (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Shrimp is a  very important export  commodity with  high market value world wide. However, it is still facing problem related to the waste and deterioration quality as main issues for the shrimp industry. In this experiment, polyphenoloxidase from the carapace of Penaeus monodon was extracted and characterized. The research was carried out to obtain the optimum extraction condition and to evaluate the properties of enzyme i.e., pH, optimum temperature for activating enzyme, kinetic enzyme, and chelating on metal ion. The best method for PPO enzyme extraction used buffer with 1:3  proportion.  The optimum activity of enzyme was at pH 7 and temperature of 35°C. The kinematic enzyme (Km) value and the maximum substrate concentration were 5.42 mM and 7.5 mM, respectively.  Na+, Ca2+, Zn2+, and EDTA with concentration 5 and 10 mM inhibited enzyme activity.  Cu2+at concentration of 10 mM and Mn2+ at concentration 5 mM also inhibited enzyme activity Keywords: carapace, characterization, polyphenoloxidase, shrimp